Mølleparken: A Settlement of the Fourth/Fifth Centuries AD at Løgumkloster, South Jutland - Wulff, Steen; Rieck, Flemming (Journal of Danish Archaeology, 1984)
Mølleparken - A Settlement of the Fourth/Fifth Centuries AD at Løgumkloster, South Jutland